Producing music - Hepworth-Sawyer, Russ; Hodgson, Jay; Marrington, Mark 1971- (Perspectives on music production series, 2019)
During the last two decades, the field of music production has attracted considerable interest from the academic community, more recently becoming established as an important and flourishing research discipline in its own right. Producing Music presents cutting-edge research across topics that both strengthen and broaden the range of the discipline as it currently stands. Bringing together the academic study of music productionand practical techniques, this book illustrates the latest research on producing music. Focusing on areas such as genre, technology, concepts, and contexts of production, Hepworth-Sawyer, Hodgson, and Marrington have compiled key research from practitioners and academics to present a comprehensive view of how music production has established itself and changed over the years